The Impact of Prenatal Dental Care Education on Oral Health Knowledge and Practices Among Pregnant Women in Cuiabá, Mato Grosso, Brazil - João Guilherme Medeiros; Aurélio Rosa da Silva Júnior; Victoria Giovana Campos; Lorena Souza Castro Altoé; Matheus Correia Casotti; Elizeu Fagundes de Carvalho; Raman Bedi; Iúri Drumond Louro; Débora Dummer Meira; Sonia Groisman (American Journal of Health Promotion, 2026)
Purpose To evaluate the effect of an educational intervention based on the Oral Health and Your Pregnancy booklet on the knowledge, attitudes, and behaviors of pregnant women in primary care in Cuiabá, Brazil. Design Quantitative pre-post intervention study without a control group. Setting A primary healthcare unit in Cuiabá, Mato Grosso, Brazil. Sample 374 pregnant women in the first to third trimester. Intervention A 30-minute lecture and practical demonstration of oral hygiene. Measures Sociodemographic questionnaire, indicators of oral-health and dietary knowledge/practices, and OHIP-14. Analysis Descriptive statistics, paired t-tests, Wilcoxon signed-rank tests, and chi-square tests. Results Knowledge about the relevance of oral health during pregnancy increased from 38% to 72% (χ 2 = 44.27; P < 0.001), awareness of disease transmission to newborns increased from 10% to 63% (χ 2 = 36.41; P < 0.001), and self-reported oral pain/discomfort decreased from 60% to 35% (χ 2 = 21.87; P < 0.001). Conclusion The intervention improved short-term oral-health knowledge and self-perception. The absence of a control group and immediate post-intervention assessment limit causal and long-term inferences.